The potential of Russia to increase its wheat production through cropland expansion and intensification - Florian Schierhorn (Humboldt-Universität zu Berlin, 2015)
This dissertation addresses the primary objective to systematically quantify untapped agricultural potentials in European Russia, where widespread abandoned agricultural lands and large yield gaps co-exist. We developed a spatial allocation model to produce annual cropland and cropland abandonment maps. Feeding the new maps into a dynamic vegetation model revealed that 470 Tg of carbon was sequestered in soil and vegetation due to the abandonment of 31 million hectares of cropland. Thus, the environmental consequences limit the potential for cropland expansion to abandoned cropland. We then calibrated a crop growth model for provincial wheat yields in European Russia and found average yield gaps of 1.51–2.10 t ha-1 under rainfed conditions and 3.14–3.30 t ha-1 under irrigated conditions. The cropland abandonment maps, spatial information on carbon sequestration due to cropland abandonment, and the estimates of yield gaps allowed us to estimate the potential of European Russia to increase its wheat production and to account for the carbon tradeoffs of cropland expansion. We demonstrated that European Russia can substantially increase its wheat production (up to 32 Mt under rainfed conditions). This increase is despite a limited expansion of wheat cultivation to the recently abandoned cropland to reduce the trade-off from the high carbon emissions in re-cultivating older, abandoned cropland where most carbon is stored. Therefore, intensification of the existing croplands is recommended to be the major driver for future growth in agricultural production. This dissertation can help policy makers and agribusiness owners identify areas suitable for cropland expansion, better target agricultural inputs and infrastructures, as well as guide adaptation strategies to the volatile climate conditions. Moreover, this dissertation contributes to better identifying and balancing trade-offs between environmental impacts and increasing agricultural production in European Russia. – – Die vorrangige Zielstellung dieser Dissertation war die Berechnung nicht erschlossener landwirtschaftlicher Potenziale des Europäischen Russlands. Wir haben ein räumliches Allokationsmodell entwickelt, dass die jährlichen Acker- und Ackerbrachflächen von 1991 bis 2009 kartiert. Diese Daten haben wir anschließend in ein dynamisches Vegetationsmodell integriert und damit berechnet, dass während der postsowjetischen Aufgabe von 31 Millionen Hektar Ackerland bis 2009 470 TgC in Boden und Vegetation gebunden wurden. Anschließend haben wir ein Pflanzenwachstumsmodell auf regionale Weizenerträge kalibriert und darauf basierend durchschnittliche Ertragslücken von 1.51-2.10 t ha-1 für natürliche (künstlich unbewässerte) und 3.14-3.30 t ha-1 für künstlich bewässerte Anbaubedingungen ermittelt. Die Karte der Ackerbrachflächen, räumlich-explizite Informationen über die Kohlenstoffspeicherung in Boden und Vegetation infolge der Ackerflächenaufgabe sowie unsere Ergebnisse der Ertragslückenberechnung haben wir zur Berechnung von Weizenproduktionspotenzialen verwendet. Unsere Ergebnisse zeigen, dass das Europäische Russland erhebliche Potenziale mobilisieren kann – bis zu 32 Millionen Tonnen für künstlich unbewässerte Bedingungen – obwohl ausschließlich jüngere Ackerbrachen zur Rekultivierung in unserem Modell berücksichtigt wurden. Ältere Brachflächen haben häufig große Mengen Kohlenstoff in Boden und Vegetation gespeichert; die Rekultivierung ältere Brachflächen würde zu hohen Emissionen führen. Eine wesentliche Schlussfolgerung dieser Dissertation ist daher, dass Produktionssteigerungen vorrangig durch Flächenintensivierung der bestehenden Ackerflächen erzielt werden sollten. Allerdings können die Ergebnisse dieser Arbeit helfen, Brachen für die Rekultivierung zu bestimmen, deren Rekultivierung relativ geringe Kohlenstoffemissionen nach sich ziehten. Zudem können die Ergebnisse dieser Arbeit nützlich sein, landwirtschaftliche Produktionsmittel effizienter einzusetzen.
urn:nbn:de:kobv:11-100233844
Keywords: 550; Russland; Landnutzungswandel; Kohlenstoffbindung; LPJml; Ertragslücken; SWAT; Weizenpotentiale; Russia; carbon sequestration; Land-use change; yield gaps; wheat potentials